مجامع الأنغام في الشعر الفلسطيني المعاصر - أبو جحجوح، خضر محمد (جامعة القدس المفتوحة, 2013)
يهدف البحث إلى تتبع توظيف الأوزان الشعرية المتنوعة، في الشعر الفلسطيني المعاصر، تحت باب مجامع الأنغام، ومحاولة الكشف عن قيمه النغمية الدالة، في مضمار التوظيف الإيقاعي، بما يتناسب مع الدفقات الشعورية التي تشكل مجموعة القصائد، في عينة الدراسة، التي تنوعت نغمات صياغتها الموسيقية. كما يهدف إلى رفد المشهد النقدي العربي المعاصر بمقاربة نقدية تنطلق من النصوص وتسجيلي ملامحها الموسيقية. \ كما طبق المنهج الوصفي التحليلي، بالغوص في بنية النصوص، وتتبع أشكال صياغتها الموسيقية، وبيان التوشجات العضوية بين الأنغام، وسلسلة التناغنات، والانسجامات المختلفة، التي سوغت الانتقال من نغم إلى نغم عند تشكيل القصائد. The research aims to follow the use of variety in the poetic meters in the \ modern Palestinian poetry which comes under the melodies section varieties. \ It also tries to disclose the value of the tonal function in the area of rhythmic \ employment which suits the emotional streams that form the set of poems \ of the sample of the study. It also aims to supply the contemporary Arab \ critical scene with a critical study which clarifies the musical features in the \ poetic texts. The descriptive analytical approach has been applied by diving \ into the text structure, following its musical forms drafting and clarifying the \ harmony between melodies and the different harmonies which justify moving \ from one tune to another in the formation of the poems.
Keywords: الشعر العربي -- العصر الحديث -- الشعراء الفلسطينيون -- نقد الشعر -- الأوزان الشعرية